Old Problem, New Concerns: Hypercortisolemia in the Time of COVID-19 - Berlińska, Agata; Świątkowska-Stodulska, Renata; Sworczak, Krzysztof (Frontiers in Endocrinology, 2021)
The ongoing coronavirus disease 2019 (COVID-19) pandemic forced a change in the way we provide medical treatment. Endocrinology in the era of COVID-19 had to transform and reduce its vast potential to the absolute necessities. Medical professionals needed to update their clinical practice to provide their patients as much support and as little harm as possible in these increasingly difficult times. International expert statements were published to offer guidance regarding proper care. It was suggested to simplify the diagnostic scheme of hypercortisolemia and to modify the approach to treatment. Hypercortisolemic patients with COVID-19 and iatrogenic hypercortisolemia due to glucocorticoid use are important clinical scenarios – we aimed to provide a cohesive summary of issues to consider.